Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo de la carrera de Pedagogía de las ciencias experimentales Informática de la Facultad de la Educación el Arte y la Comunicación 2023-2024 - Armijos Solis, Kevin Alexander (2024)
This Curricular Integration Project entitled : BASIC COGNITIVE PROCESSES AND READING COMPREHENSION IN FIRST-YEAR STUDENTS OF THE PEDAGOGY IN EXPERIMENTAL SCIENCES - COMPUTER SCIENCE PROGRAM AT THE FACULTY OF EDUCATION, ART, AND COMMUNICATION 2023-2024. aimed to analyze the relationship between the levels of basic cognitive processes, specifically selective attention and working memory, and the levels involved in reading comprehension: literal comprehension, reorganization of information, inferential comprehension, critical comprehension, and appreciative comprehension in first-year students of the Pedagogy in Experimental Sciences - Computer Science Program at the Faculty of Education, Art, and Communication, during the 2023- 2024 academic year. This research adopted a descriptive correlational and cross-sectional mixed-methods approach, with a non-experimental design. The study was conducted with a non-probabilistic sample of twenty-seven students, who were administered the D2 Test of Attention, the memory subscale of the Reynolds Intellectual Assessment Scales (RIAS), and the ICLAU Reading Comprehension Assessment. The results indicated that 93% of the students exhibited low levels of selective attention, and 56% demonstrated low levels of working memory. Regarding reading comprehension, 70% of the participants exhibited low levels. The data revealed a Kendall's Tau-b correlation coefficient of 0.45 between selective attention and the levels associated with reading comprehension, indicating a moderate positive correlation. Meanwhile, the correlation between working memory and the levels associated with reading comprehension showed a Kendall's Tau-b value of 0.38, indicating a low positive correlation. In conclusion, the results suggest a moderate positive correlation between selective attention and reading comprehension, and a low positive correlation between working memory and reading comprehension, underscoring the importance of addressing these cognitive processes with psychoeducational interventions.